Does the Philippine stock market respond to domestic economic fundamentals and regional equities markets? An ARDL bound testing approach - Tomaliwan, Maria Francesca D. (Animo Repository, 2016)
This paper aims to study the impact of domestic macroeconomic factors, regional and advanced economies’ equity markets on the Philippine stock market behavior. Monthly data from January 2006 to December 2013 of four macroeconomic variables namely industrial production index, money supply, short term interest rate and exchange rate; four regional equity markets returns of Thailand, Singapore, Indonesia and Malaysia; and lastly two advanced economies’ equity market returns of Hong Kong and the United States of America were used in the study. By applying the Autoregressive Distributed Lag (ARDL) method and vector error correction model (VECM), it showed co-integration between Philippine stock market and aforementioned factors which meant a long-run equilibrium relationship existed. In the Granger causality sense, money supply and the Singapore stock market affects the Philippine stock prices in the long-run as well as in the short-run.